Development of ArcGIS StoryMaps as Digital-based Innovative Learning Media - Yamres Pakniany; Heinrich Rakusa (Journal Education Innovation (JEI), 2024)
The development of ArcGIS StoryMaps as a Digital-based Innovative Learning Media is a study that explores the potential of utilizing this digital narrative platform in improving the quality of education. In the increasingly connected and technology-based context of modern education, ArcGIS StoryMaps provides a powerful tool for visualizing and explaining information through the incorporation of maps, images, text, video and audio in the form of interactive narratives. This research uses a descriptive qualitative approach. The type of research used is a literature study which is research that has been done before by collecting journal books, magazines, and scientific papers that are interrelated with the problems and research objectives. The results of this study discuss the basic concepts of ArcGIS StoryMaps, the development of learning materials, implementation in learning, challenges that may be faced, as well as recommendations and guidelines for further development. It is hoped that the results of this research will provide a deep insight into how the use of StoryMaps can enrich students' learning experience and improve their preparation for an increasingly connected and digital future.